A Practicable Implementation of Training and Development in Professional Services: The Case of Accountants in Cyprus - Theodorou, Loucas; Vrontis, Demetris; Christofi, Michael (My University, 2019)
The aim of this empirical research is to identify whether the investment of organisations in training and development (T&D) practices affects the retention of professional accountants in Cyprus by their current employers. The results show that the congruence between employee interests and training programmes and the level of investment in T&D are the two major elements of T&D that have a significant positive impact on employee retention. Congruence between employee interests and training programmes in comparison with the level of investment in T&D affects employee retention more. However, both elements are significantly important. This study provides guidelines to practitioners in order to develop and implement their HR and T&D strategy that will assist them to achieve the desired sustainable competitive advantage.
Keywords: Accountants